PEREMPUAN KAPUK DALAM EKSPEKTASI BUDAYA PATRIARKI (SEBUAH ANALISIS BEBAN GANDA GENDER) - Huda, Khoirul; Renggani, Linda Ayu (Kafa`ah: Journal of Gender Studies, 2021)
Women's problems can never be separated from the context of the dual context that is delegated to them. Matters related to injustice in providing distribution of workloads, as the application of an excessive patriarchal culture. As a result, there is an imbalance in the treatment of men to women, so that they are vulnerable to violence. As is the case with women selling Kapuk in Tapelan Village who are charged with the main task of earning a living. They are relied on in supporting the family economy. However, the situation reversed when the Covid-19 epidemic hit the world so that it changed the order of economic life, including improving by Kapok women. What needs to be considered during a pandemic is by implementing staying at home, whether they keep working by maximizing natural products or are they given a dual role in the family. Together they are also faced with patrilineal bonds that must obey the orders of their husbands. This study aims to analyze the form of the double burden of Kapok women during the Covid-19 pandemic. The research method uses a library research approach. Data collection refers to library materials from research reports, archives and books of Sikep Tapelan women (2017), Sikep women in Blora Regency (2018), and women warriors Samin Margomulyo (2019).Furthermore, it is criticized in order to obtain interpretation data so as to produce scientific conclusions. The results showed that Kapok women face a double burden that is too heavy especially household chores. They face the roles and functions in the family as companions to their husbands, carry out family affairs, assist with children's education, and help with economic welfare. Opening a simple shop, doing business from home crops, and agricultural labor as additional work. In practice, they still face and bear the double burden of doing domestic work which is getting higher.